HUBUNGAN DURASI KERJA MENYETRIKA TERHADAP TERJADINYA GEJALA CARPAL TUNNEL SYNDROME PADA PEKERJA LAUNDRY DI KOTA BALIGE - Dwi Arihta Sari Bangun; Trisno Susilo; Ronald Erwansyah (Jurnal Kesehatan dan Fisioterapi, 2023)
Background: Carpal Tunnel Syndrome (CTS) is a common work-related disorder caused by repetitive movements and sedentary positions for long periods of time that can affect the nerves, blood supply to the hand and wrist. The National Health Interview Study (NIHS) estimates the prevalence of CTS in the adult population to be 1.55% (2.6 million). Meanwhile, in Indonesia, the incidence of carpal tunnel syndrome until 2001 is still very difficult to know with certainty due to the lack of data. Duration of work is one of the factors that cause symptoms of Carpal Tunnel Syndrome. The purpose of this study was to determine the relationship between the duration of ironing work on the occurrence of symptoms of Carpal Tunnel Syndrome in Laundry Workers in Balige City. The research design uses Analytical Observational with a Correlational approach or Correlation . The population and sample in this study amounted to 40 people. Based on the results of the study, it is known that there is a relationship between the duration of ironing and the occurrence of symptoms of Carpal Tunnel Syndrome in laundry employees in the city of Balige. This can be seen from the results of the SPSS test, it is found that the P value is 0.000. So it can be concluded that the value is smaller than 0.05, which means it is known that there is a strong relationship between work duration and the occurrence of Carpal Tunnel Syndrome symptoms in Laundry Employees in Balige City.Keywords: Duration of Work, Symptoms of CTS